Preparation method of pure-phase sulfide solid-state electrolyte, solid-state electrolyte and solid-state battery
通过在硫化物固态电解质制备中,将LiX与硫化锂在溶剂中溶解并重结晶,再与硫化磷球磨的方法,解决了现有技术中固态电解质相纯度不高的问题,实现了更高纯度和 The solid electrolyte preparation of higher ion conductivity has reduced the preparation time and energy consumption.
Patent Information
- Application Number
- CN202411958001.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sulfide solid electrolyte preparation methods cannot effectively solve the problem of the miscellaneous phases generated during the reaction, resulting in the low purity of the solid electrolyte phase.
The method of dissolving lix and lithium sulfide in alcohol solvents, after heavy crystallization and sulfide ball grinding, ensure that the raw materials are fully mixed and uniform, and then fully react and reduce the production of miscellaneous phases during the sintering process.
The sulfide solid electrolyte prepared through this method has higher phase purity and ionic conductivity, reducing the preparation time and energy consumption.
Smart Images

Figure CN119370812A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a method for preparing a pure-phase sulfide solid electrolyte, a solid electrolyte and a solid battery. Background Art
[0002] Up to now, sulfide solid electrolytes have become an important research object in the current solid-state battery industry due to their highest ionic conductivity among solid electrolytes and their characteristics such as low Young's modulus.
[0003] In the application of sulfide solid electrolytes, not only the positive and negative electrode materials are required to have very high phase purity, but also the sulfide solid electrolyte materials themselves have extremely high phase purity requirements. This requires that in the preparation process of sulfide solid electrolytes, in addition to ensuring the high purity phase of the raw materials, the raw materials must also be completely reacted during the preparation reaction without generating other impurities. The currently used preparation methods such as high-energy ball milling, high-temperature sintering, and liquid phase methods, although they can achieve batch preparation and can achieve a high purity, cannot solve the problem of generating impurities during the reaction and cannot meet the requirements of high purity phases. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a pure phase sulfide solid electrolyte, a solid electrolyte and a solid battery, so as to solve the problem that the solid electrolyte prepared by the existing preparation method has low phase purity.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a pure phase sulfide solid electrolyte comprises the following steps: Weigh LiX, phosphorus sulfide and lithium sulfide required for synthesizing sulfide solid electrolyte in molar ratio, where X is Cl, Br or I; Dissolving LiX and lithium sulfide in an alcohol solvent to obtain a mixed solution; The mixed solution is dried to obtain a mixed powder of LiX and lithium sulfide recrystallization; ball-milling the mixed powder and phosphorus sulfide to obtain a precursor material for preparing a sulfide solid electrolyte; heating the precursor material to a temperature required for the precursor material to react, thereby obtaining a pure phase sulfide solid electrolyte; The operations in the above steps are all carried out in an inert gas atmosphere.
[0006] In some embodiments, the alcohol solvent is one or more of ethanol, methanol, and isopropanol.
[0007] In some embodiments, the mass ratio of the sum of the mass of LiX and lithium sulfide to the mass of the alcohol solvent is 1:1-20.
[0008] In some embodiments, it is characterized in that the mass ratio of the sum of the masses of LiX and lithium sulfide to the alcohol solvent is 1:4.
[0009] In some embodiments, the precursor material is heated to 500° C.-600° C. and kept warm for 0.5-5 hours to obtain a pure phase sulfide solid electrolyte.
[0010] In some embodiments, the precursor material is heated to 500° C. and kept at this temperature for 1 hour to obtain a pure phase sulfide solid electrolyte.
[0011] In some embodiments, the precursor material is heated at a heating rate of 8-10° C. / min to a temperature required for reacting the precursor material.
[0012] In some embodiments, the mixed powder, phosphorus sulfide and zirconium oxide beads are put into a ball mill together, and ball milled at a rotation speed of 100-500 rpm for 0.5-5 hours to obtain a precursor material for preparing a sulfide solid electrolyte.
[0013] In some embodiments, the mixed powder, phosphorus sulfide and zirconium oxide beads are ball-milled in a ball mill at a rotation speed of 500 rpm for 1 hour to obtain a precursor material for preparing a sulfide solid electrolyte.
[0014] On the other hand, the present invention also provides a pure phase sulfide solid electrolyte prepared by the pure phase sulfide solid electrolyte preparation method.
[0015] On the other hand, the present invention also provides a solid-state battery, comprising the prepared pure-phase sulfide solid electrolyte.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects: In the preparation method of the present invention, LiX and lithium sulfide are mixed at the molecular level in a solvent, and then recrystallized to fully mix LiX and lithium sulfide to obtain a mixed powder with good uniformity; then, the mixture is ball-milled and mixed with phosphorus sulfide with a low melting point and sintered to obtain a sulfide solid electrolyte. Since LiX and lithium sulfide are fully mixed through recrystallization, the precursor material obtained by ball milling has good uniformity, and the three materials are mixed evenly, which ensures that the three materials can fully react without residue during the sintering process, thereby ensuring that the prepared solid electrolyte has high phase purity.
[0017] By recrystallizing LiX and lithium sulfide, LiX and lithium sulfide are fully mixed, which reduces the time required for ball milling. After ball milling, the particle size of the precursor material is smaller, thereby reducing the time required for the sintering process and reducing the energy consumption required for preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 The EIS graphs of the performance tests in the embodiments and comparative examples of the present invention are shown in FIG. 1 , FIG. 2 , and FIG. 3 , respectively. S1, S2, and S3 represent the embodiment 1, the embodiment 2, and the embodiment 3, respectively. D1 represents the comparative example 1. The abscissa represents the impedance, and the ordinate represents the reactance.
[0020] Figure 2 The XRD diagrams of the performance tests in the embodiments and comparative examples of the present invention are shown in FIG. 1 , FIG. 2 , and FIG. 3 , respectively. S1, S2, and S3 represent embodiment 1, embodiment 2, and embodiment 3, respectively. D1 represents comparative example 1. The abscissa represents the degree of the peak, and the ordinate represents the intensity of the peak. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0022] Currently, sulfide solid electrolytes are usually prepared by solid-phase reaction method, which has the problems of complex synthesis process, time-consuming and energy-consuming, and the generation of impurities due to insufficient reaction.
[0023] After research, it was found that when using the solid phase reaction method to prepare sulfide solid electrolytes, taking the sulfide solid electrolyte Li6PS5Cl as an example, its generation is based on Li2S as the crystal nucleus, and the melting points of LiCl and Li2S in the raw materials are relatively high, much higher than the temperature for preparation and sintering, while the melting point of P2S5 is relatively low. During preparation and sintering, it is liquid and close to the boiling point. Therefore, in the process of preparing Li6PS5Cl, the particle size of the raw materials and the uniformity of the mixing have an important influence on whether the raw materials can fully react with each other, especially the particle size and uniformity of LiCl and Li2S.
[0024] At present, ball milling is usually adopted to ensure the particle size of the raw materials and the uniformity of mixing between the raw materials by fully ball milling the raw materials. This not only takes a long time for ball milling and consumes a lot of energy, but also the raw material mixing effect is not ideal, so that the raw materials cannot fully react during sintering, resulting in the sulfide solid electrolyte prepared by sintering unable to meet the requirements of high purity phase.
[0025] In the present invention, LiCl and Li2S are dissolved in a solution, so that LiCl and Li2S can be mixed at the molecular level in the solution, and then LiCl and Li2S are recrystallized and precipitated. The recrystallized LiCl and Li2S can be fully mixed and have good uniformity; and further ball milling is performed to fully mix them with P2S5 with a low melting point. In this way, during sintering preparation, the raw materials can fully react with each other without the problem of residue, thereby ensuring the phase purity of the prepared sulfide solid electrolyte.
[0026] In some embodiments of the present invention, a method for preparing a pure phase sulfide solid electrolyte comprises the following steps: S01, weigh LiX, phosphorus sulfide and lithium sulfide required for synthesizing sulfide solid electrolyte in molar ratio, X is Cl, Br or I; S02, dissolving LiX and lithium sulfide in an alcohol solvent to obtain a mixed solution; S03, drying the mixed solution to obtain a mixed powder of LiX and lithium sulfide recrystallization; S04, ball-milling the mixed powder and phosphorus sulfide to obtain a precursor material for preparing a sulfide solid electrolyte; S05. Heat the precursor material to a temperature required for the precursor material to react, and obtain a pure phase sulfide solid electrolyte, such as Li6PS5X.
[0027] The operations in the above steps are all carried out in an inert gas atmosphere to prevent the raw materials from reacting with other external substances during the operation.
[0028] In some embodiments, in step S02, the alcohol solvent is one or more of ethanol, methanol, and isopropanol.
[0029] In some embodiments, in step S02, the mass ratio of the sum of the masses of LiX and lithium sulfide to the alcohol solvent is 1:1-20, that is, the mass ratio of the solid (LiX and lithium sulfide) to the liquid (alcohol solvent) is 1:1-20. For example, the mass ratio of the sum of the masses of LiX and lithium sulfide to the alcohol solvent can be 1:4, 1:5 or 1:10 or other ratios, so that LiX and lithium sulfide are fully mixed in the solution and the time required for drying is reduced.
[0030] In step S03, the mixed solution may be dried by subjecting the mixed solution to rotary evaporation in a rotary evaporator or other similar drying methods.
[0031] In some embodiments, in step S04, the mixed powder, phosphorus sulfide and zirconium oxide beads are put into a ball mill together, and ball milled at a rotation speed of 100-500 rpm for 0.5-5 hours to obtain a precursor material for synthesizing a sulfide solid electrolyte.
[0032] For example, the mixed powder, phosphorus sulfide and zirconium oxide beads are ball-milled at 500 rpm for 1 hour in a ball mill to obtain a precursor material for synthesizing a sulfide solid electrolyte; or ball-milled at 250 rpm for 1.5 hours; or ball-milled at 200 rpm for 2 hours, etc.
[0033] The mass ratio of the zirconium oxide beads to the raw materials (mixed powder and phosphorus sulfide) is 10-50: 1. In some embodiments, the mass ratio of the zirconium oxide beads to the total raw materials may be 10: 1, 20: 1 or 30: 1.
[0034] In some embodiments, in step S05, the precursor material is heated to 500°C-600°C at a heating rate of 8-10°C / min, and then kept warm for 0.5-5h. For example, in the sintering operation step, the precursor material prepared in step S04 is heated to 500°C in a high-temperature furnace at a heating rate of 8°C / min, and then kept warm for 1h; or heated to 600°C at a heating rate of 10°C / min, and then kept warm for 0.5h, or heated to 550°C at a heating rate of 9°C / min, and then kept warm for 3h.
[0035] During the preparation process, the precursor material obtained by ball milling is transferred to a high-temperature furnace together with zirconium oxide beads for sintering. After the sintering is completed, the temperature is naturally cooled to room temperature, and then the prepared material and the zirconium oxide beads are separated to obtain a pure phase sulfide solid electrolyte.
[0036] The preparation process of the method for preparing the pure phase sulfide solid electrolyte of the present invention is described in detail below in conjunction with specific examples and comparative examples.
[0037] Example 1 In this embodiment, the preparation of sulfide solid electrolyte Li6PS5Cl is taken as an example, and the preparation method of Li6PS5Cl includes the following steps: S01, weigh 0.7914g LiCl, 2.0695g P2S5, 2.13905g Li2S; S02, fully dissolving the above LiCl and Li2S in 20g of anhydrous ethanol to obtain a mixed solution; S03, drying the mixed solution by rotary evaporation using a rotary evaporator to obtain a recrystallized mixed powder of LiCl and Li2S; S04, adding the mixed powder obtained in the above step, P2S5 and 50g of zirconium oxide beads into a ball mill, and ball milling at a speed of 500rpm for 1h to obtain a precursor material for preparing Li6PS5Cl; S05, transferring the above-obtained precursor material and 50g of zirconium oxide beads to a high-temperature furnace, heating to 500°C at a heating rate of 8°C / min, keeping the temperature for 1h, and naturally cooling to room temperature; The prepared material is taken out and separated into balls to obtain the sulfide solid electrolyte Li6PS5Cl.
[0038] Example 2 The method for preparing Li6PS5Cl in this embodiment comprises the following steps: S01, weigh 0.7914g LiCl, 2.0695g P2S5, 2.13905g Li2S; S02, fully dissolving the above LiCl and Li2S in 20g of anhydrous ethanol to obtain a mixed solution; S03, drying the mixed solution by rotary evaporation using a rotary evaporator to obtain a recrystallized mixed powder of LiCl and Li2S; S04, adding the mixed powder obtained in the above step, P2S5 and 50g of zirconium oxide beads into a ball mill, and ball milling at a speed of 100rpm for 1h to obtain a precursor material for preparing Li6PS5Cl; S05, transferring the above-obtained precursor material and 50g of zirconium oxide beads to a high-temperature furnace, heating to 500°C at a heating rate of 8°C / min, keeping the temperature for 1h, and naturally cooling to room temperature; The prepared material is taken out and separated into balls to obtain the sulfide solid electrolyte Li6PS5Cl.
[0039] Example 3 The method for preparing Li6PS5Cl in this embodiment comprises the following steps: S01, weigh 0.7914g LiCl, 2.0695g P2S5, 2.13905g Li2S; S02, fully dissolving the above LiCl and Li2S in 20g of anhydrous ethanol to obtain a mixed solution; S03, drying the mixed solution by rotary evaporation using a rotary evaporator to obtain a recrystallized mixed powder of LiCl and Li2S; S04, adding the mixed powder obtained in the above step, P2S5 and 50g of zirconium oxide beads into a ball mill, and ball milling at a speed of 500rpm for 1h to obtain a precursor material for preparing Li6PS5Cl; S05, transferring the above-obtained precursor material and 50g of zirconium oxide beads to a high-temperature furnace, heating to 500°C at a heating rate of 8°C / min, keeping the temperature for 0.5h, and naturally cooling to room temperature; The prepared material is taken out and separated into balls to obtain the sulfide solid electrolyte Li6PS5Cl.
[0040] Comparative Example 1 In Comparative Example 1, Li6PS5Cl is prepared by an existing solid phase reaction preparation method, comprising the following steps: S01, weigh 0.7914g LiCl, 2.0695g P2S5, 2.13905g Li2S; S02, the weighed raw materials and 50g of zirconium oxide beads were ball-milled in a ball mill at a speed of 500rpm for 1h to obtain a precursor material for preparing Li6PS5Cl; S03, transferring the above-obtained precursor material and 50g of zirconium oxide beads to a high-temperature furnace, heating to 500°C at a heating rate of 8°C / min, keeping the temperature for 1h, and naturally cooling to room temperature; The prepared material is taken out and separated into balls to obtain the sulfide solid electrolyte Li6PS5Cl.
[0041] The performance of the sulfide solid electrolyte Li6PS5Cl prepared in the above embodiment and comparative example was tested, including: 1) Ionic conductivity test The sulfide solid electrolyte Li6PS5Cl prepared above was placed in a glove box with a water content of less than 0.1 ppm, and was unidirectionally pressed at a pressure of 220 MPa to form an electrolyte sheet with a diameter of 10 mm and a thickness of 0.4 mm; Stainless steel sheets with a certain degree of flexibility were placed at both ends of the electrolyte sheet, and bidirectional pressure was applied at a pressure of 60 MPa to assemble a blocked electrode battery.
[0042] The prepared blocked electrode battery was subjected to an AC impedance test, and the ionic conductivity was calculated according to the formula σ=L / RS, where σ is the conductivity, L is the thickness of the electrolyte sheet, R is the resistance of the electrolyte sheet tested by EIS, and S is the cross-sectional area of the electrolyte sheet.
[0043] The EIS test results of the electrolyte sheet are as follows: Figure 1 As shown; wherein, S1, S2, S3 represent Example 1, Example 2 and Example 3 respectively, and D1 represents Comparative Example 1.
[0044] from Figure 1 It can be seen that the resistance value of the EIS test of the blocked electrode battery of Li6PS5Cl in Example 1, Example 2 and Example 3 is smaller than the resistance value of Li6PS5Cl prepared by the conventional preparation method in Comparative Example 1; according to the calculation formula of ionic conductivity, it can be seen that the ionic conductivity of Li6PS5Cl prepared in Examples 1-3 is greater than that of Comparative Example 1.
[0045] 2) XRD test The sulfide solid electrolyte prepared as above was placed in a glove box with water and oxygen content lower than 0.1 ppm, and the sulfide solid electrolyte was evenly spread on a glass sample table for a sealing test.
[0046] The peak change from 10 θ to 80 θ was measured at a rate of 10 θ / min and then compared with the Li6PS5Cl standard card.
[0047] The XRD test results of solid electrolyte materials are as follows: Figure 2 As shown; wherein, S1, S2, S3 represent Example 1, Example 2 and Example 3 respectively, and D1 represents Comparative Example 1.
[0048] Figure 2 The peak at 27 degrees corresponds to Li2S, and the peak at 35 degrees corresponds to LiCl.
[0049] from Figure 2 It can be seen that the peak intensities corresponding to Li2S and LiCl in Li6PS5Cl prepared in Examples 1-3 are lower, indicating that Li2S and LiCl react fully and have higher purity.
[0050] Through performance comparison tests, the preparation method of the present invention mixes the solid-phase raw materials in the reaction at the molecular level before sintering. Compared with the existing preparation method, the prepared sulfide solid electrolyte has higher phase purity and ionic conductivity, and greatly reduces the time required for preparation and reduces the required energy consumption.
[0051] On the other hand, some embodiments of the present invention also provide a pure-phase sulfide solid electrolyte prepared by the above preparation method.
[0052] On the other hand, some embodiments of the present invention further provide a solid-state battery, which uses the pure-phase sulfide solid electrolyte prepared as described above.
[0053] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0054] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0055] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0056] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A method for preparing a pure phase sulfide solid electrolyte, characterized in that: The following steps are involved: Weigh LiX, phosphorus sulfide and lithium sulfide required for synthesizing sulfide solid electrolyte in molar ratio, where X is Cl, Br or I; Dissolving LiX and lithium sulfide in an alcohol solvent to obtain a mixed solution; The mixed solution is dried to obtain a mixed powder of LiX and lithium sulfide recrystallization; ball-milling the mixed powder and phosphorus sulfide to obtain a precursor material for preparing a sulfide solid electrolyte; heating the precursor material to a temperature required for the precursor material to react, thereby obtaining a pure phase sulfide solid electrolyte; The operations in the above steps are all carried out in an inert gas atmosphere.
2. The method for preparing a pure phase sulfide solid electrolyte according to claim 1, characterized in that: The alcohol solvent is one or more of ethanol, methanol and isopropanol.
3. The method for preparing a pure phase sulfide solid electrolyte according to claim 2, characterized in that: The mass ratio of the sum of the mass of LiX and lithium sulfide to the mass of the alcohol solvent is 1:1-20.
4. The method for preparing a pure phase sulfide solid electrolyte according to claim 2, characterized in that: The mass ratio of the sum of the mass of LiX and lithium sulfide to the mass of the alcohol solvent is 1:
4.
5. The method for preparing a pure phase sulfide solid electrolyte according to claim 1, characterized in that: The precursor material is heated to 500°C-600°C and kept warm for 0.5-5h to obtain a pure phase sulfide solid electrolyte.
6. The method for preparing a pure phase sulfide solid electrolyte according to claim 1 or 5, characterized in that: The precursor material is heated at a heating rate of 8-10° C. / min to a temperature required for the precursor material to react.
7. The method for preparing a pure phase sulfide solid electrolyte according to claim 1, characterized in that: The mixed powder, phosphorus sulfide and zirconium oxide beads are put into a ball mill together, and ball milled at a rotation speed of 100-500 rpm for 0.5-5 hours to obtain a precursor material for preparing a sulfide solid electrolyte.
8. The method for preparing a pure phase sulfide solid electrolyte according to claim 7, characterized in that: The mixed powder, phosphorus sulfide and zirconium oxide beads were ball-milled in a ball mill at a rotation speed of 500 rpm for 1 hour to obtain a precursor material for preparing a sulfide solid electrolyte.
9. A pure phase sulfide solid electrolyte prepared by the method for preparing a pure phase sulfide solid electrolyte according to any one of claims 1 to 8.
10. A solid-state battery, characterized in that Comprising the pure phase sulfide solid electrolyte as described in claim 9.
Citation Information
Patent Citations
Method of producing sulfide solid electrolyte material
CN108242561A
Efficient preparation method of sulfur halide compound solid electrolyte
CN114163240A
Preparation method of sulfide electrolyte, sulfide electrolyte and application of sulfide electrolyte
CN114455613A
Sulfide solid electrolyte precursor, sulfide solid electrolyte preparation method and battery
CN118763271A
Sulfide solid electrolyte, preparation method thereof and battery
CN119306192A
Cited By
Modified sulfide solid electrolyte and preparation method and application thereof
CN120280542A